A weight-of-evidence approach for identifying potential sources of untreated sewage inputs into a complex urbanized catchment. (15th April 2021) - Codello, Annachiara; McLellan, Sandra L.; Steinberg, Peter; Potts, Jaimie; Scanes, Peter; Ferguson, Angus; Hose, Grant C.; Griffith, Merran; Roguet, Adelaide; Lydon, Keri A.; Maher, William A.; Krikowa, Frank; et al.
Abstract: The Hawkesbury-Nepean River (HNR) is the largest catchment in the Sydney region and is undergoing unprecedented population growth. The HNR system receives a mix of anthropogenic inputs such as treated sewage, stormwater and agricultural runoff. Combined, these can diminish the ecological system health and pose potential concerns to human health. Of particular concern are inputs of untreated sewage, that can occur due to a range of different reasons including illegal point source discharges, failure of the sewerage network, and overloading of wastewater treatment plants during storm events. Here, we present findings of an intensive assessment across the HNR catchment where we used a weight-of-evidence (WOE) approach to identify untreated sewage contamination in surface waters against the background of treated effluent and diffuse inputs during post high flow conditions. Total nitrogen and phosphorus concentrations were used to assess treated effluent and diffuse inputs, and microbial analysis, including both culture-based traditional methods for E. coli and enterococci and qPCR analysis of Bacteroides and Lachnospiraceae, were used to assess raw sewage contamination. Despite a background of diffuse inputs from recent high flow events and the influence of treated wastewater, we found no gradient of faecal contamination along the HNR system or its tributaries. We observed two sites with evidence of untreated sewage contamination, where the human markers Bacteroides and Lachnospiraceae qPCR copy numbers were high. The biological and chemical approaches suggested these latter two hotspots originate from an industrial runoff source and possibly from a dry weather sewage leak. Our findings demonstrate the potential of a WOE approach in the assessment of human faecal signal in an urban river that can also pinpoint small sources of contamination as a strategy that can reshape the way monitoring is performed and the chemical end-points chosen to provide pertinent information on the potential risks to aquatic system health. Graphical abstract: Image 1 Highlights: Weight-of-evidence approach proved useful for identifying sewage contamination. Chemical measures alone are insufficient to conclude the presence of sewage. The nutrient can not pinpoint the source of contamination. Human markers address the ambiguity between, physicochemical and biological information. Abstract : A multiple lines of evidence approach is required to capture both human and ecological risks, and human-specific bacteria qPCR assays can reduce the ambiguity in detecting untreated sewage.